2012
DOI: 10.1002/agr.21291
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attitudinal and Sociodemographic Factors on the Likelihood of Buying Locally Produced Food

Abstract: This study explores the factors associated with Canadian consumers locally produced food purchase intention. Data from an Internet-based survey of consumers (n = 1,139) was analyzed using a bivariate probit model. The bivariate probit model related attitudinal, behavioral and sociodemographic factors to the intention to purchase fresh and nonfresh locally produced foods. Although sociodemographic characteristics play a limited role in shaping local food purchase intentions, attitudinally based variables have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 41 publications
10
75
2
5
Order By: Relevance
“…In fact, deeper quantitative analysis showed that South Tyrolean rural consumers place significantly more importance on quality compared with the other groups. The high consideration of this attribute confirms previous evidence pointing to quality and better taste as main drivers motivating consumers to purchase local food (Adams-Adams 2011, Cranfield et al 2012, Feldmann-Hamm 2015.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In fact, deeper quantitative analysis showed that South Tyrolean rural consumers place significantly more importance on quality compared with the other groups. The high consideration of this attribute confirms previous evidence pointing to quality and better taste as main drivers motivating consumers to purchase local food (Adams-Adams 2011, Cranfield et al 2012, Feldmann-Hamm 2015.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies associated more supportive attitudes towards local food in elderly respondents living in rural areas (Racine et al 2013, Megicks et al 2012, MirosaLawson 2012, Khan-Prior 2010, Tregear-Ness 2005, Brown 2003, Wolf 1997, with women generally exhibiting more positive attitudes than men (Cholette et al 2013, Pelletier et al 2013, Cranfield 2012, Bellows et al 2010). Notably Chambers et al (2007) 'could not identify any differences in attitudes between urban and rural consumers' (Feldmann-Hamm 2015: 156).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the sample of college students, findings should still prove useful. Cranfield et al (2012) suggest that attitudes are more important than socioeconomic factors in predicting local food purchasing habits, while demographic variables do not seem to be important in predicting local food purchases (Brown, 2003). Participants were recruited on a volunteer basis via announcements through instructors of several general education courses at a large, public university.…”
Section: Participants and Incentivesmentioning
confidence: 99%
“…Although a definition of local foods is somewhat ambiguous and often personalized by individual consumers depending upon their local market and product (Cranfield, Henson, & Blandon, 2012;Martinez, 2010), several common, broad purchase motivators became apparent after a comprehensive review of the literature. Messages highlighting empirically established purchase motivators in local food messaging might invoke a stronger intent to purchase locally grown food.…”
mentioning
confidence: 99%